The Malaysia MOOC Initiative : The Universiti Malaysia Sarawak Experience - Chuah, Kee Man; Johari, Abdullah; Emmy Dahliana, Hossain; Ang, Tse Chwan; Noorhaslina, Senin (Routledge, 2019)
As one of the pioneers for Malaysia MOOC, Universiti Malaysia Sarawak (UNIMAS) has gained valuable insights as to how MOOC can be designed and developed effectively to meet the current educational demands. Since its first MOOC in 2013, the UNIMAS MOOC team aspires to ensure quality MOOCs are produced without ignoring the need to introduce localized contents to the global audience. This chapter outlines the philosophy behind each MOOC published by UNIMAS, which includes the instructional principles as well as content development steps. Future MOOCs produced by UNIMAS will continue to uphold its principle of injecting local essence by further emphasizing the unique and diverse communities in Sarawak, Malaysia.